Screening for Activity Against AMPA Receptors Among Anticonvulsants—Focus on Phenytoin - Dron, M. Y.; Zhigulin, A. S.; Tikhonov, D. B.; Barygin, O. I. (Frontiers in Pharmacology, 2021)
The interest in AMPA receptors as a target for epilepsy treatment increased substantially after the approval of perampanel, a negative AMPA receptor allosteric antagonist, for the treatment of partial-onset seizures and generalized tonic-clonic seizures. Here we performed a screening for activity against native calcium-permeable AMPA receptors (CP-AMPARs) and calcium-impermeable AMPA receptors (CI-AMPARs) among different anticonvulsants using the whole-cell patch-clamp method on isolated Wistar rat brain neurons. Lamotrigine, topiramate, levetiracetam, felbamate, carbamazepine, tiagabin, vigabatrin, zonisamide, and gabapentin in 100-µM concentration were practically inactive against both major subtypes of AMPARs, while phenytoin reversibly inhibited them with IC50 of 30 ± 4 μM and 250 ± 60 µM for CI-AMPARs and CP-AMPARs, respectively. The action of phenytoin on CI-AMPARs was attenuated in experiments with high agonist concentrations, in the presence of cyclothiazide and at pH 9.0. Features of phenytoin action matched those of the CI-AMPARs pore blocker pentobarbital, being different from classical competitive inhibitors, negative allosteric inhibitors, and CP-AMPARs selective channel blockers. Close 3D similarity between phenytoin and pentobarbital also suggests a common binding site in the pore and mechanism of inhibition. The main target for phenytoin in the brain, which is believed to underlie its anticonvulsant properties, are voltage-gated sodium channels. Here we have shown for the first time that phenytoin inhibits CI-AMPARs with similar potency. Thus, AMPAR inhibition by phenytoin may contribute to its anticonvulsant properties as well as its side effects.